Turning likes into lifts: Understanding how adolescents experience fitfluencer content and the opportunities it offers them - Marloes de Brabandere; Ini Vanwesenbeeck; Liselot Hudders (International Journal of Qualitative Studies on Health & Well-Being)
Current research on fitfluencers and fitspiration content is mostly quantitative and emphasizes its negative impact, overlooking its opportunities. Adolescents, who are undergoing an important and delicate developmental period, are largely understudied in research on fitfluencers and fitspiration. Combined with more than 80% of the world’s adolescents not being sufficiently physically active, more research is needed on how fitfluencers may positively impact adolescents’ mental and physical health. Through 20 semi-structured in-depth interviews with adolescents (aged 14–18), this study explores their lived experiences with fitfluencers and the role these play in their mental and physical health, and which opportunities fitfluencers offer to positively impact adolescents. Adolescents reported minimal negative consequences of fitfluencers and experience more motivation than demotivation. Four main opportunities—information, authenticity, actionable content, and entertainment—incited motivation to exercise and make fitfluencers’ appearance and lifestyle more attainable and relatable. These results can guide future research on how fitfluencers can positively affect adolescents.